Postoperative speech impairment and cranial nerve deficits in children undergoing posterior fossa tumor surgery with intraoperative MRI - a prospective multinational study - Laustsen, Aske Foldbjerg; Grønbæk, Jonathan Kjær; Frič, Radek; Avula, Shivaram; Mallucci, Conor; Nilsson, Pelle; Nyman, Per; Hauser, Péter; Mudra, Katalin; Kiudeliene, Rosita; Ročka, Saulius; Hjort, Magnus Aasved; et al. (Acta neurochirurgica, 2025)
BACKGROUND: Postoperative speech impairment (POSI) and cranial nerve deficits (CND) are common complications of pediatric posterior fossa (PF) tumor surgery. Intraoperative MRI (ioMRI) has proven a useful tool in achieving gross total resection. The risk of POSI and CND with ioMRI remains unclear, making it the primary scope of this study. Additionally, we assessed whether POSI was associated with CND. METHODS: We prospectively included pediatric patients undergoing PF tumor surgery in 36 centers across 15 European countries. Neurological status and speech were assessed preoperatively and 1-4 weeks postoperatively. Surgical details, including tumor location and use of ioMRI, were recorded within 72 h of surgery. Postoperative CND were categorized as 0, 1, 2, or ≥ 3 nerves affected; POSI as habitual, reduced speech, or mutism. Proportional odds models estimated odds ratios (OR) for 1) POSI with stepwise adjustment for tumor location and age, and 2) CND with adjustment for preoperative CND and tumor location. Subgroup analyses assessed systematic differences, missing data, center-level effects, and histology adjustment. RESULTS: Of 790 primary PF tumor surgeries, 141 (18%) involved ioMRI. POSI occurred in 183/790 (23%) and postoperative CND in 213/790 (27%). POSI-risk with ioMRI showed non-significant unadjusted OR (95% CI) 0.83 (0.53;1.30); adjusted OR 0.76 (0.43;1.35). Fewer CNDs were observed with ioMRI (unadjusted OR 0.63 (0.40;1.00), adjusted OR 0.58 (0.33;0.94), p = 0.03). POSI-risk was associated with more CNDs (adjusted OR for 1 CND: 2.06 (1.15;3.68); 2 CND: 2.13 (1.02;4.42); ≥ 3 CND: 4.15 (1.98;8.70), p < 0.05). CONCLUSIONS: ioMRI was not associated with increased risk of postoperative complications in this multicenter cohort. The reduction in CND among ioMRI cases may reflect derived effects on surgical decision-making, expertise, case-load and case-mix. Results should be interpreted with caution due to limited intraoperative data. The association between POSI-risk and cumulative CND may indicate extensive brainstem involvement. Our findings highlight the need to further explore how ioMRI-guided strategies affect functional outcomes in pediatric PF tumour surgery. CLINICAL TRIALS ID: NCT02300766 (October 2014).
Keywords: Infratentorial Neoplasms; Infant; Pediatric Neurosurgery; Prospective Studies; Posterior Fossa Tumor; předškolní dítě; nemoci kraniálních nervů; Humans; Magnetic Resonance Imaging; Cerebellar mutism syndrome; poruchy řeči; Speech Disorders; prospektivní studie; Europe; magnetická rezonanční tomografie; infratentoriální nádory; mužské pohlaví; Intraoperative Magnetic Resonance Imaging; Child, Preschool; Cranial Nerve Deficits; neurochirurgické výkony; Adolescent; Evropa; Cranial Nerve Diseases; Postoperative Complications; ženské pohlaví; Neurosurgical Procedures; pooperační komplikace; lidé; mladiství; Posterior Fossa syndrome; dítě; Child; Male; kojenec; Female